Pancreatic tuberculosis mimicking pancreatic malignancy in an immunocompromised patient: A case report - Sebastian, Sherin; Kulkarni, Tanaya; Pawar, Shephali S (Indian Journal of Case Reports, 2026)
Pancreatic tuberculosis (TB) is a rare and diagnostically challenging entity, as it can closely mimic pancreatic malignancy both clinically and radiologically. We report the case of a 40-year-old human immunodeficiency viruspositive female who presented with chronic abdominal pain. Imaging revealed a non-enhancing hypodense pancreatic lesion along with retroperitoneal lymphadenopathy, raising a strong suspicion of malignancy. Tumor markers were negative. Owing to limited resources, financial and temporal constraints, an exploratory laparotomy was performed. Intraoperative findings revealed necrotizing granulomas involving the pancreatic lesion and pancreaticoduodenal lymph nodes. Histopathological examination and microbiological analysis confirmed the diagnosis of TB. Initiation of antitubercular therapy led to rapid clinical improvement. This case highlights the diagnostic dilemma posed by pancreatic TB, particularly in resource-limited settings. It underscores the importance of maintaining a high index of suspicion for TB in endemic regions and in immunocompromised patients presenting with atypical pancreatic lesions. Early consideration of this diagnosis can help prevent misdiagnosis and unnecessary surgical interventions.